Implementation System for the Promotion of State Civil Servants in the City of Makassar - Muh.Aswar Darwis; Muhammad Yunus; Hasniati Hasniati (Institute of Computer Science (IOCS), 2021)
Promotion is a career planning process. This study aims to obtain an overview of the implementation of the promotion of the Makassar City State Civil Apparatus. The approach used is qualitative. Data obtained through direct field observations, interviews, and document analysis. The data analysis used was data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the structural position employee promotion system such as: (a) seniority can be a consideration in the implementation of employee promotion (b) educational qualifications that can support an employee's career to be promoted (c) employee loyalty with a loyal attitude towards work with the institution can become a separate consideration for occupying a higher position in the implementation of promotion, (d) the honesty of an employee of the State civil apparatus is needed in terms of promotion, because it can be related to the tasks that will be carried out when occupying a position with responsibility. greater (e) work performance which is always accompanied by rewards to employees both individually and as an organization, because this reward can improve the performance of employees in carrying out their duties, and always show the abilities they have. iki and can be one of the assessments in the implementation of promotion. Factors that influence (a) Nepotism System (b) Politics (Spoil System), the employees who will be promoted should be avoided from political factors so that the implementation of promotions for employees runs according to established procedures.